Trade liberalisation round 1973 - Manfred Holthus (Intereconomics, 1973)
The GATT Minister Conference to be held in Tokyo from September 12 to 14 will be the prelude to a new round of international negotiations about further liberalisation of world trade. Preparatory work of some six years thus comes to its conclusion.
Keywords: 330; Foreign Trade